Meta-Analisis Pengaruh Model Pembelajaran Role Playing pada Proses Pembelajaran Berbicara Siswa Sekolah Dasar - Yohanna Nirmalasari; Triwati Rahayu; Alvian Guntur Prasetya Aziz; Riswanda Himawan; Muhammad Afnani Alfian (Universitas PGRI Semarang, 2025)
This study aims to determine the effect of role playing strategies on language learning, particularly on students' speaking skills. This study is a meta-analysis of the results obtained from 20 scientific journals. The data analysis technique in this study used a comparative method to determine the impact of the use of role-playing strategies on students' speaking skills. Furthermore, a paired sample t-test was used to see the average increase before and after classroom activities, as well as to determine whether there were differences in the average of the two paired or related groups. The analysis results showed that the average percentage increase in student learning outcomes with the role-playing strategy increased students' speaking skills from the lowest 7.06% to the highest 76.74% with an average increase of 33.05%. Students' speaking skills after using the role-playing strategy increased significantly by 18.82%. Based on the data analysis, it can be concluded that the role-playing strategy can have a positive effect on improving students' speaking skills.